Real-World Evidence of Hertone™: A Homeopathic Uterotonic for Functional and Hormonal Disorders of the Female Reproductive System (Advancements in Homeopathic Research, 2025)
Introduction: Functional gynecological disorders such  as menstrual irregularities, hormonal imbalance, and  unexplained infertility are increasingly prevalent due  to lifestyle and environmental factors. Homeopathic  formulations offer non-hormonal alternatives with  minimal adverse effects. Hertone™, a homeopathic  uterotonic developed by Schwabe India, is indicated  for a range of female reproductive conditions. This  study aimed to assess its clinical effectiveness and  safety in real-world settings through a post marketing  physician survey. Methods: A structured questionnaire using  Google Forms was circulated among prescribing  homeopathic physicians across India. The survey  captured responses from 131 doctors on parameters  including effectiveness, speed of action, adverse  effects, recommendation likelihood, and prescription  frequency. Data were analyzed using descriptive  statistics. Results: Among the 131 doctors, 93.9% rated  Hertone™ with a score of 4 or 5 for effectiveness,  indicating high satisfaction with its clinical benefits.  Regarding onset of action, 81.7% reported noticeable  therapeutic effects within three days. Adverse effects  were rare, with 95.4% reporting no undesirable  outcomes. Furthermore, 90.8% of doctors affirmed  recommending Hertone™, and 84.73% had  prescribed it more than 25 times, highlighting its  high acceptance in regular practice. Conclusion: The findings suggest that Hertone™  is a well-tolerated, non-hormonal homeopathic  formulation with favorable clinical outcomes in  managing functional and hormonal reproductive  disorders. Its widespread recommendation and  frequent prescriptions reinforce its relevance as a  safe adjunct in women's reproductive healthcare.
Keywords: Hertone™; Homeopathy; Uterotonic; Menstrual Irregularities; PCOS; Female Reproductive Health